Archaeologies of Island Melanesia Current approaches to landscapes, exchange and practice - Leclerc, Mathieu; Flexner, James (Terra Australis, 2019)
Island Melanesia is a remarkable region in many respects, from its great ecological and linguistic diversity, to the complex histories of settlement and interaction spanning from the Pleistocene to the present. Archaeological research in Island Melanesia is currently going through a vibrant phase of exciting new discoveries and challenging debates about questions that apply far beyond the region. This volume draws together a variety of current perspectives in regional archaeology for Island Melanesia, focusing on Vanuatu, the Solomon Islands, New Caledonia and Papua New Guinea. It features both high-level theoretical approaches and rigorous data-driven case studies covering recent research in landscape archaeology, exchange and material culture, and cultural practices.